2016
DOI: 10.1177/0044118x16646590
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Race and Community Poverty and Its Effects on Adolescents’ Academic Achievement

Abstract: Although most studies have established the importance of individual-level influences on adolescent outcomes, studies are often limited in that they do not address the effects of broader community-level factors. To address this limitation, we examined the association between community-level poverty and adolescents' academic achievement, and the role of race in this association. Results from multilevel modeling suggested that (a) regardless of community type (i.e., low vs. high poverty), Black adolescents report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…White adolescents had better OHL compared with their non-white counterparts. A previous study found that non-white adolescents had a poorer academic performance and called attention to the occurrence of racial difference regarding the academic performance of economically underprivileged adolescents 27 . Such social inequalities occur in many societies, affecting the social inclusion of non-white individuals.…”
Section: Discussionmentioning
confidence: 99%
“…White adolescents had better OHL compared with their non-white counterparts. A previous study found that non-white adolescents had a poorer academic performance and called attention to the occurrence of racial difference regarding the academic performance of economically underprivileged adolescents 27 . Such social inequalities occur in many societies, affecting the social inclusion of non-white individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Though student academic achievement is lower in high-poverty RM and non-RM communities alike, Black students report lower academic achievement regardless of poverty status compared to white students. 53 This reinforces that additional factors sabotage academic success for RM students, 53 impacting health long-term.…”
Section: T a G G E D H 2 Gentrificationt A G G E D E N Dmentioning
confidence: 85%
“…In students aged 8 to 10 years old, adaptability is one of the factors that contribute to academic achievement, and in students aged 11 to 13 years old, the factors that contribute to academic achievement are stress management ability, intrapersonal emotional intelligence, and adaptability (Brouzos, Misailidi, & Hadjimattheou 2014). Other factors that can affect academic achievement are socioeconomic status, learning style, selfconfidence, adaptability, and social competence (Chen, Huang, Chang, Wang, & Li 2010;von Stumm, et al, 2011;Brouzos, et al, 2014;Gordon & Cui, 2016).…”
Section: Discussionmentioning
confidence: 99%